An occult intracranial foreign body introduced via a conjunctival wound. (July 2013) - Vaqas, Babar; Kopniczky, Zsolt; Haliasos, Nik; Namnyak, Simon; Pollock, Jonathan
We present a case of a 23-year-old man who suffered a facial assault. An intracranial foreign body, a socket from a socket wrench, was introduced into the cranial cavity via a medial conjunctival entry wound which presented with minimal physical signs. The entry wound and the foreign body were missed during the patient's first presentation to an emergency department leading to a delay in diagnosis. Subsequent periorbital swelling and visual blurring prompted delayed investigation leading to detection of the foreign body. This case report highlights the need for a high index of suspicion of intracranial complications when assessing ocular injuries. The mechanism of the penetrating injury, the ophthalmological findings and the surgical and antibiotic management are discussed.